Potential model application and planning issues - Christiane Weber; Jacky Hirsch (Cybergeo, 2000)
Interaction models and especially potential model have often been used for demographic or social purposes, in order to study the relationships dimension between population types and locations or between users and goods etc. Defining the interactions between space characteristics, Donnay (1997, 1995, 1994) and Binard (1995) have promoted the application of such model on remote sensing products in order to obtain urban delimitation. Another use of potential model also dealing with remotely sensed product has been proposed by Weber et al. (1997  ; Weber, 1998) by the integration of potential model principles and GIS capacities to evaluate development trends of an urban settlement over years. In this case GIS is used to diversify the importance of locations taken into account over the studied area. This could be defined by spatial information (as initial input) and other characteristics attached: urban regulation, environment protection laws, urban development trends etc. This allows multiplying the current visions of urban area development. Referring to natural constrains or anthropic decisions such approach offers the possibility to integrate different types of interactions between various locations. Statistical methods are applied to get land-cover classification results of the images used, then potential model is processed in order to obtain potential surfaces associated with specific spatial characteristics. The resulting layers might be combined to get composed information on the area or ordered results.The application presented has been conducted on the Strasbourg region in order to assess the method according the city development reality. A time analysis has been set up linked to spatial changes evaluation. Dynamic processes have been identified through sequential estates (1986 – 1998). The potential model application is used to get a more predictive idea of the spatial changes reality, allocating diverse weights to landscape locations. Two satellite images have been used : the first one to get a first idea of the land-cover surface on Strasbourg and the surroundings (SPOT XS 1986), and the second one has been processed (1) to perform time series analysis and (2) to assess the accuracy of the potential model application (SPOT XS 1998). Ancillary data are gathered in order to enrich our knowledge on the studied area through environmental, planning or demographic points of view.The expected results are the identification of development trends from potential model application on remotely sensed results. Point to be stressed is the determination of the location weights according to spatial characteristics. Methods considered to deal with the combination of weights are close to multicriteria analysis.